Human T lymphotropic virus type 1 and risk of cardiovascular disease: High‐density lipoprotein dysfunction versus serum HDL‐C concentrations. (29th January 2019) - Samadi, Sara; Abolbashari, Samaneh; Meshkat, Zahra; Mohammadpour, Amir Hooshang; Kelesidis, Theodoros; Gholoobi, Aida; Mehramiz, Mehrane; Tabadkani, Mahla; Sadabadi, Fatemeh; Dalirfardouei, Razieh; Ferns, Gordon A; Ghayour‐Mobarhan, Majid; et al.
Abstract: High‐density lipoprotein (HDL) is thought to be protective against cardiovascular disease (CVD), and HDL dysfunction is considered to be a risk factor for CVD. It is unclear whether there is an association between Human T lymphotropic virus type 1( HTLV1) infection and CVD risk. We have assessed HDL lipid peroxidation (HDLox) as a marker of HDL dysfunction and CVD risk in a subgroup of the MASHAD cohort study. One hundred and sixty two individuals including 50 subjects positive for HTLV1 infection and 112 individuals negative for HTLV1 infection were recruited. Anthropometric and biochemical parameters including serum hs‐CRP, fasted lipid profile (HDL‐C, LDL, triglycerides, and cholesterol), and fasting blood glucose were determined. Serum HDLox was also measured in the study participants. Multivariate analyses were used to evaluate the association between serum HDLox and HTLV1 infection. None of the traditional CVD risk factors were associated with HTLV1 infection, including serum HDL‐C. However, serum HDLox was independently associated with the presence of HTLV1 infection. Logistic regression analysis showed that subjects who were positive for HTLV1 infection were also significantly more likely than uninfected individuals to have higher HDLox (odds ratio 9.35, 95%CI: 3.5–24.7; P < 0.001). HDLox was increased approximately 20% ( P < 0.001) in infected subjects compared to the uninfected group. Serum HDLox is a marker of CVD risk factor and increased in individuals affected by HTLV1 infection compared to healthy subjects. © 2019 BioFactors, 45(3):374–380, 2019